Modulation of TGF-β/Smad and Nrf2 Signaling Pathways by Thymoquinone in the Attenuation of Renal Fibrosis: A Systematic Review and Meta-Analysis of Pre-clinical Models - Chairil Makky; Ian Effendi; Zulkhair Ali; Novadian; Suprapti (HM Publisher, 2026)
Background: Renal fibrosis is the irreversible, final common pathway for all progressive forms of chronic kidney disease (CKD), leading to end-stage renal disease. Its pathogenesis is characterized by the over-activation of pro-fibrotic signaling, chiefly the Transforming Growth Factor-beta (TGF-β)/Smad pathway, and the failure of endogenous cytoprotective mechanisms like the nuclear factor erythroid 2-related factor 2 (Nrf2) antioxidant response. Thymoquinone (TQ), the primary bioactive constituent of Nigella sativa, is a pleiotropic compound with known anti-inflammatory and antioxidant properties. This study was designed to systematically quantify its mechanistic efficacy in modulating the core Nrf2 and TGF-β pathways in established pre-clinical models of renal fibrosis and injury. Methods: We conducted a systematic review and meta-analysis following PRISMA guidelines. We performed a comprehensive search of major databases (including PubMed and Scopus) for pre-clinical in vivo studies published between 2014 and 2025 that investigated TQ monotherapy or TQ-dominant combination therapy in rodent models of renal injury. The eight studies that met the inclusion criteria utilized diverse models: Unilateral Ureteral Obstruction (UUO), cisplatin-induced nephrotoxicity, gentamicin-induced nephrotoxicity, 5-fluorouracil (5-FU)-induced acute kidney injury (AKI), lipopolysaccharide (LPS)-induced inflammation, carfilzomib (CFZ)-induced renal impairment, and ischemia-reperfusion (IRI). Primary outcomes were the expression of renal Nrf2 and TGF-β1. Secondary outcomes included markers of fibrosis (collagen deposition, histology scores), renal function (BUN, creatinine), oxidative stress (MDA, SOD, GSH, CAT), and inflammation (TNF-α, NF-κB, IL-6, IL-1β). Data were pooled using a random-effects model, and primary analyses were stratified by injury model subgroup. Results: Thymoquinone treatment resulted in a profound and significant upregulation of the protective Nrf2 pathway (SMD: 2.38; 95% CI [1.05, 3.71]; p < 0.001; 3 studies) and its downstream target Heme Oxygenase-1 (HO-1). Concurrently, TQ treatment markedly suppressed the primary pro-fibrotic driver, TGF-β1 (SMD: -2.09; 95% CI [-2.99, -1.19]; p < 0.001; 2 studies). This pivotal dual modulation translated into significant functional and structural improvements. TQ robustly attenuated renal fibrosis scores (SMD: -1.89; 95% CI [-2.55, -1.23]; p < 0.001; 2 studies). Stratified subgroup analysis showed TQ significantly improved renal function in both chemotoxic AKI models (BUN SMD: -2.31; 95% CI [-3.22, -1.40]) and chronic obstructive/fibrosis models (BUN SMD: -1.17; 95% CI [-1.75, -0.59]). This functional protection was underpinned by potent, broad-spectrum reversal of oxidative stress and inflammation across all subgroups. Conclusion: Thymoquinone consistently ameliorates renal injury and fibrosis across a wide spectrum of pre-clinical models. Its mechanism of action is multifaceted, critically involving the dual modulation of opposing pro-fibrotic and protective pathways: it suppresses the TGF-β1 cascade while simultaneously activating and restoring the Nrf2 antioxidant response. This body of evidence strongly supports Thymoquinone as a high-potential candidate for translational research and development as a novel, network-targeting therapy for human renal fibrosis.